MicroRNA-218 inhibits the malignant phenotypes of glioma by modulating the TNC/AKT/AP-1/TGFβ1 feedback signaling loop - Dang, Siwen; Zhang, Rui; Tian, Sijia; Hou, Peng; Li, Gang; Ji, Meiju (International journal of molecular medicine, 2021)
Gliomas are the most malignant and common tumors of the human brain, and the prognosis of glioma patients is extremely poor MicroRNAs (miRNAs or miRs) play critical roles in different types of cancer by performing post-transcriptional regulation of gene expression Although miR-218 has been demonstrated to be decreased in gliomas, its role in gliomas remains largely unknown miR-218 expression was analyzed in gliomas and normal brain tissues (control subjects) using a dataset from The Cancer Genome Atlas A series of in vitro and in vivo studies were performed to determine the biological roles of miR-218 in glioma cells Potential targets of miR-218 were identified using a dual-luciferase reporter system Western blot and dual-luciferase reporter system experiments were performed to evaluate the regulatory effect of miR-218 on the tenascin C (TNC)/AKT/activator protein 1 (AP-1)/transforming growth factor β1 (TGFβ1) pathway It was demonstrated that miR-218 was significantly downregulated in gliomas compared with control subjects, and played potent tumor suppressor roles in glioma cells by inhibiting cell proliferation, colony formation, migration, invasion and tumorigenic potential in nude mice, as well as inducing cell cycle arrest and apoptosis Mechanistically, miR-218 inhibited malignant phenotypes of glioma cells by binding to the 3′-untranslated region of its target TNC and subsequently suppressing its expression As a result, miR-218 could reduce AKT phosphorylation and subsequently inhibit transcriptional activity of AP-1 by reducing JNK phosphorylation, downregulating the expression of TGFβ1, while TGFβ1 was able to, in turn, activate the TNC/AKT/AP-1 signaling axis Our data revealed a previously unknown tumor suppressor role of miR-218 by blocking the TNC/AKT/AP-1/TGFβ1-positive feedback loop in glioma